0.4-V bulk-driven differential-difference amplifier. Issue 5 (May 2015) - Kulej, Tomasz; Khateb, Fabian
Abstract A new solution for an ultra-low-voltage, low-power, bulk-driven fully differential-difference amplifier (FDDA) is presented in the paper. Simulated performance of the overall FDDA for a 50 nm CMOS process and supply voltage of 0.4 V, shows dissipation power of 31.8 μW, the open loop voltage gain of 58.6 dB and the gain-bandwidth product (GBW) of 2.3 MHz for a 20 pF load capacitance. Despite the very low supply voltage, the FDDA exhibits rail-to-rail input/output swing. The circuit performance has also been tested in two applications; the differential voltage follower and the second-order band-pass filter, showing satisfactory accuracy and dynamic range.